( 2x - 3 ) 3 = 125
(2x - 3 ) 3 = 53
2x - 3 = 5
2x = 5 + 3
2x = 8
x = 8 : 2
x = 4
\(\left(2x-3\right)^3=125\)
\(\left(2x-3\right)^3=5^3\)
\(2x-3=5\)
\(2x=5+3\)
\(2x=8\)
\(x=8:2\)
\(x=4\)
(2x - 3)3 = 125
2x - 3 = 5
2x = 8
x = 4
\(\left(2x-3\right)^3=125\)
\(\Rightarrow2x^3-3^3=125\)
\(\Rightarrow2x^3-9=125\)
\(\Rightarrow2x^3=125+9\)
\(\Rightarrow2x^3=134\)
\(\Rightarrow x^3=\frac{134}{2}\)
\(\Rightarrow x^3=67\)
\(\Rightarrow x=...\)
(2x-3)33=125
(2x-3)27=125
2x-3 =125X27
2x-3 =3375
2x =3375+3
2x =3378
x =3378:2
x = 1689
Nếu có gì sai bạn nhắn tin lại cho mình đễ mình sửa nha
(2x-3)3=125
Mà: 53=125
=>(2x-3)3=53
=> 2x-3=5
=>2x=5+3
=>2x=8
=>x=8:2
=>x=4